Pendampingan Membaca Huruf Hijaiyah dengan Metode ABCD (Asset-Based Community Development) di Madrasah Diniyah Hidayatu at Thulab Dayakan - Muhammad Alifan Ahzari; Wahyudi (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This community service program was initiated to strengthen students’ basic Qur’anic literacy by assisting them in recognizing and reading hijaiyah letters at Madrasah Diniyah Hidayatu At Thulab Dayakan. The main objective was to overcome students’ early reading challenges while at the same time empowering the local community through the Asset-Based Community Development (ABCD) approach. The program followed several stages: asset identification to map resources such as teachers, parents and available media; mobilization of these assets through collaborative meetings; capacity building for teachers and facilitators to improve phonetic skills and teaching strategies; implementation of guided reading activities in small groups and individual sessions; and evaluation to observe learning outcomes. The results demonstrated a gradual but consistent improvement in students’ ability to distinguish similar letters, articulate sounds according to correct makhraj, and memorize letter sequences more fluently. Their confidence in reading aloud also increased significantly. Furthermore, the active participation of parents. In conclusion, the Asset-Based Community Development (ABCD) method proved not only effective in enhancing hijaiyah literacy but also successful in cultivating a sustainable culture of collaborative learning within the community.